2009
DOI: 10.1111/j.1365-2311.2009.01111.x
|View full text |Cite
|
Sign up to set email alerts
|

Bottom‐up effects of glucosinolate variation on aphid colony dynamics in wild cabbage populations

Abstract: 1. There is an ongoing debate about the relative importance of top-down and bottom-up regulation of herbivore dynamics in the wild. Secondary metabolites, produced by plants, have negative effects on survival and growth of some herbivore species, causing bottom-up regulation of population dynamics. Herbivore natural enemies may use plant secondary metabolites as cues to find their prey, but their survival and reproduction can also be influenced by the upward cascade of secondary metabolites through the food we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
57
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 74 publications
5
57
1
Order By: Relevance
“…Moreover, the effect of B. brassicae-infestation on insect community waned when the season progressed in both 2012 and 2013. Seasonal variation in insect responses to plant chemical traits was also reported for the wild cabbage populations in their natural habitat in the UK (Newton et al, 2009). Plant-mediated effects on herbivores are not constant over the growing season and can be attributed to changes in herbivore densities and chemical traits of the plants .…”
Section: Community-wide Effects Of Early-season Aphid Infestation | 67mentioning
confidence: 62%
See 4 more Smart Citations
“…Moreover, the effect of B. brassicae-infestation on insect community waned when the season progressed in both 2012 and 2013. Seasonal variation in insect responses to plant chemical traits was also reported for the wild cabbage populations in their natural habitat in the UK (Newton et al, 2009). Plant-mediated effects on herbivores are not constant over the growing season and can be attributed to changes in herbivore densities and chemical traits of the plants .…”
Section: Community-wide Effects Of Early-season Aphid Infestation | 67mentioning
confidence: 62%
“…the enhanced production of aphid-induced carnivore attractants. Controlled for genotypic variation, Newton et al (2009) reported a strong positive correlation between B. brassicae density and parasitism by Diaeretiella rapae, the most common parasitoid of B. brassicae. In the present study, there was no effect of cabbage population on the population dynamics of B. brassicae in either of the two years.…”
Section: Community-wide Effects Of Early-season Aphid Infestation | 67mentioning
confidence: 99%
See 3 more Smart Citations